Air-entrainment in hydraulic intakes with a vertical pipe: The mechanism and influence of pipe offset. (January 2022) - Xianbei, Huang; Qiang, Guo; Tao, Fang; Xurui, Chen; Baoyun, Qiu
Highlights: The air-entrained vortex formation procedures are consistent despite of the different pipe positions. The vortex movement is dominated the vorticity tilting effect. For the pipe-offset cases, the natural asymmetry characteristics makes the entrainment formation more easily and quickly. For the pipe-centered cases, the asymmetric flow arises due to the asymmetric flow separation near pipe surface. Abstract: Air-entrainment is a negative phenomenon in hydraulic intakes with a vertical pipe. Researchers sometimes chose to offset the pipe from the intake center to trigger the air-entrainment, while the underlying mechanism on the formation and propagation is not fully understood. In this paper, the mechanism in both pipe-offset and pipe-centered cases is studied in depth. In addition, the asymmetric flow generated in the symmetric pipe-centered cases is analyzed. It is found that the air-entrained vortex formation procedures are consistent despite of the different pipe positions. The formation and enhancement of the air-entrainment is decided by the stretching term in the enstrophy transport equation. The movement of the vortex is closely related to the tilting term. Asymmetric flow is classical characteristics no matter whether the pipe located on the centerline of the intake or not. For the pipe-offset cases, the natural asymmetry makes the air-entrainment formation more easily and quickly. The relative air-entrainment rate is found to be larger in pipe-offset cases than in pipe-centered cases. For the pipe-centered cases, the asymmetric flow arises due to the asymmetric flow separation when the flow past the pipe surface. The study extends the generality of the formation procedure proposed by Guo et al. (2020). In addition, the flow separation effect on the air-entrained vortex is revealed. If one can suppress the separation, the air-entrained vortex is expected to be suppressed simultaneously.